Compound and method for producing the same, and composite material

By adjusting the composition of Zr2.00-bMbSYPZO12.00+δ compound, it ensures that it displays negative thermal expansion rate in different temperature ranges and improves insulation resistance, the problem of insufficient performance of existing negative thermal expansion materials in the high temperature range is solved. Thermal expansion control and insulation performance improvement under complex temperature conditions are achieved.

CN115667150BActive Publication Date: 2025-02-25MITSUI MINING & SMELTING CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180037455.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-06-22
Filing Date
2021-04-05
Publication Date
2025-02-25
Estimated Expiration
2041-04-05

AI Technical Summary

Technical Problem

Existing negative thermal expansion materials generally show positive thermal expansion in addition to specific temperature areas, and the negative thermal expansion performance in the high temperature range is insufficient, making it difficult to meet the thermal expansion control needs under complex temperature conditions.

Method used

A new compound composed of Zr2.00-bMbSYPZO12.00+δ was proposed. By adjusting the amount of M element, the amount of sulfur and the amount of phosphorus, the compound is ensured at room temperature ~ 100°C, room temperature ~ 200°C or room temperature ~ 300°C. A negative thermal expansion rate is shown in the area and an insulation resistance is improved.

Benefits of technology

It achieves significantly excellent negative thermal expansion rates in different temperature ranges, meets the thermal expansion control needs under complex temperature conditions, and improves insulation resistance, which is suitable for thermal expansion management of high-precision electronic equipment and composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003955986770000181
    Figure BDA0003955986770000181
  • Figure BDA0003955986770000191
    Figure BDA0003955986770000191
Patent Text Reader

Abstract

The present invention provides a novel compound that exhibits a negative coefficient of thermal expansion and has a high insulation resistance. It is a compound represented by the compositional formula Zr 2.00‑ b M b S Y P Z O 12.00+δ (wherein M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, Mo; 0 ≤ b < 2.00, 0 < Y < 0.30, Z ≥ 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition), or a compound represented by the compositional formula Zr 2.00‑b M b S Y P Z O 12.00+δ (wherein M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, Mo; 0 ≤ b < 2.00, 0.30 ≤ Y ≤ 1.00, Z > 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel compound showing a negative thermal expansion coefficient in which the volume decreases as the temperature rises, a method for producing the same, and a composite material using the novel compound. Background Art

[0002] In the technical field requiring precision such as electronic equipment, optical equipment, fuel cells, sensors, etc., for example, when a plurality of raw materials are combined to form equipment, if dislocation, interface peeling, disconnection, etc. are generated due to the difference in thermal expansion coefficient between the raw materials, it is likely to become a serious problem. Therefore, a control technology for thermal expansion is required. As one of the thermal expansion control technologies, the technology of combining materials with negative thermal expansion coefficients (also referred to as "negative thermal expansion materials") to control the overall thermal expansion coefficient has attracted attention.

[0003] Most substances increase in volume due to thermal expansion when the temperature rises. In contrast, there are few negative thermal expansion materials that have the property of decreasing in volume when heated.

[0004] However, even if they are called negative thermal expansion materials, generally speaking, most of them show negative thermal expansion only in a certain temperature range and show positive thermal expansion in other temperature ranges.

[0005] As negative thermal expansion materials, for example, β-eucryptite, zirconium tungstate (ZrW2O8), zirconium tungstate phosphate (Zr2WO4(PO4)2), Zn x Cd 1-x (CN)2, manganese nitride, bismuth, nickel, iron oxides, etc.

[0006] In addition, Patent Document 1 discloses Bi as a new negative thermal expansion material. 1-x Sb x NiO3 (wherein x is 0.02≤x≤0.20).

[0007] Patent Document 2 discloses a compound as a new negative thermal expansion material, characterized in that Zr 2- a M a S x P2O 12+δ (M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, and Cr, a is 0≤a<2, x is 0.4≤x≤1, and δ is a value specified in a manner that satisfies the charge neutrality condition (electrical neutrality condition)).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2017-48071

[0011] Patent Document 2: WO2019 / 167924A1 Summary of the Invention

[0012] Problems to be Solved by the Invention

[0013] At present, using the negative thermal expansion material as described above, more excellent low thermal expansion property is required. In addition, with the miniaturization of components, the thinning of wiring is progressing, and higher insulation is also required.

[0014] In addition, the negative thermal expansion material disclosed in Patent Document 2 above is the following material, and thus is attracting attention as a useful material: it shows a negative thermal expansion rate in the range of room temperature to 500 °C, and the larger the sulfur content (x), the more it shows a negative thermal expansion rate especially at 100 to 180 °C, and low density can also be achieved.

[0015] On the other hand, in specific applications, materials that show a negative thermal expansion rate especially in the temperature range of room temperature to 100 °C, room temperature to 200 °C, or room temperature to 300 °C are required. For example, when controlling the thermal expansion rate of a resin material, when a negative thermal expansion material is added to the resin material as a positive thermal expansion material to adjust the thermal expansion rate, in the case where the melting point or glass transition temperature of the resin material is low, a negative thermal expansion material that shows a negative thermal expansion rate in the temperature range of room temperature to 100 °C, room temperature to 200 °C, or room temperature to 300 °C is required.

[0016] Therefore, the present invention provides a novel compound made of a composition different from the conventional one, which shows a negative thermal expansion rate and has a high insulation resistance.

[0017] More preferably, a novel compound having a high insulation resistance and further showing a particularly excellent negative thermal expansion rate especially in the temperature range of room temperature to 100 °C, room temperature to 200 °C, or room temperature to 300 °C is provided.

[0018] Means for Solving the Problems

[0019] To solve the above problems, the present invention provides a compound (referred to as "Compound 1 of the present invention"), which is represented by the compositional formula Zr 2.00-b M b S Y P Z O 12.00+δ (In the formula, M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, Mo, 0 ≤ b < 2.00, 0 < Y < 0.30, Z ≥ 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition).

[0020] The present invention also provides a compound (referred to as "compound 2"), which is composed of the formula Zr 2.00-b M b S Y P Z O 12.00+δ (wherein, M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, and Mo, 0≤b<2.00, 0.30≤Y≤1.00, Z>2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition).

[0021] Effects of the Invention

[0022] The present compounds 1 and 2 proposed by the present invention both show negative thermal expansion coefficients. Therefore, the thermal expansion coefficient of the composite material as a mixture can be controlled by mixing with a material showing a positive thermal expansion coefficient (referred to as a "positive thermal expansion material"). In addition, the present compounds 1 and 2 both have excellent insulation resistance and can be effectively used in the technical field requiring insulation resistance.

[0023] Furthermore, the present compound 1 proposed in the present invention shows a significantly excellent negative thermal expansion coefficient in the temperature range of room temperature to 100° C. Therefore, it can be suitably used for controlling the thermal expansion coefficient in the temperature range of room temperature to 100° C. For example, it is possible to implement the control of the thermal expansion coefficient in the temperature range of room temperature to 100° C. of a composite material obtained by mixing with a positive thermal expansion material.

[0024] In addition, the present compound 2 proposed in the present invention shows a significantly excellent negative thermal expansion coefficient in the temperature range of room temperature to 200°C and room temperature to 300°C. Therefore, it can be suitably used for controlling the thermal expansion coefficient in the temperature range of room temperature to 200°C and room temperature to 300°C. For example, it is possible to implement the control of the thermal expansion coefficient in the temperature range of room temperature to 200°C and room temperature to 300°C of a composite material obtained by mixing with a positive thermal expansion material. DETAILED DESCRIPTION

[0025] Next, the present invention will be described based on the embodiment examples. However, the present invention is not limited to the embodiment described below.

[0026] <Present compound 1>

[0027] Hereinafter, a compound which is an example of an embodiment of the present invention (referred to as "the present compound 1") will be described in detail.

[0028] The present compound 1 is composed of the formula Zr 2.00-b M b S Y P ZO 12.00+δ A compound represented by (where 0 ≤ b < 2.00, 0 < Y < 0.30, Z ≥ 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition).

[0029] In the compositional formula of this Compound 1, when b = 0, it becomes Zr 2.00 S Y P Z O 12.00+δ A compound represented by (where 0 < Y < 0.30, Z ≥ 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition). On the other hand, when 0 < b < 2.00, it becomes a compound in which a part of the Zr sites is substituted by M.

[0030] In the compositional formula of this Compound 1, M is preferably one or a combination of two or more selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, and Mo.

[0031] Zr 2.00 S Y P Z O 12.00+δ A compound obtained by substituting a part of the Zr sites in (where 0 < Y < 0.30, Z ≥ 2.00) with these elements M as described above shows a negative thermal expansion rate in the same manner as the compound in which the Zr sites contain only Zr, and high insulation resistance can be achieved.

[0032] In the compositional formula of this Compound 1, "b" representing the amount (atomic ratio) of the M element is preferably 0 or more and less than 2.00, more preferably 0 or more and less than 1.50, still more preferably 0 or more and less than 1.00, and yet more preferably 0 or more and less than 0.80.

[0033] In the compositional formula of this Compound 1, "Y" representing the amount (atomic ratio) of S (sulfur) is preferably greater than 0 and less than 0.30, more preferably 0.10 or more and less than 0.30, still more preferably 0.15 or more and less than 0.30, and yet more preferably 0.20 or more and less than 0.30.

[0034] Furthermore, "Z" representing the amount (atomic ratio) of P (phosphorus) is preferably 2.00 or more, more preferably more than 2.40. On the other hand, it is preferably 3.50 or less, more preferably 3.00 or less, still more preferably 2.80 or less.

[0035] In addition, "δ" in the compositional formula of the present Compound 1 is a value defined in a manner that satisfies the charge neutrality condition, and is generally -2.50 to 1.00. Sometimes it is particularly -2.00 or more or 0.50 or less, more particularly -1.50 or more or 0.00 or less, still more particularly -1.50 or more or -0.50 or less, and yet more particularly more than -1.33 or less than -0.80. It should be noted that the "charge neutrality condition" may not be completely neutral, and compositions with oxygen deficiency or oxygen excess within the range allowable for a compound are permitted.

[0036] The amounts of each element other than oxygen, namely Zr, M, S, and P, can be measured by dissolving the total amount and using ICP - OES. In addition, since it is difficult to strictly measure the amount of oxygen, a compositional ratio presumed to be electrically neutral from the chemical ratios of the elements other than oxygen is set.

[0037] As the crystal phase present in Compound 1, α - Zr2SP2O 12 phase (ICDD card number: 04 - 017 - 0937 or / and ICDD card number: 00 - 038 - 0489) can be cited. Preferably, this crystal is the main phase, that is, in the X - ray diffraction pattern obtained by analyzing Compound 1 by X - ray diffraction method (XRD, Cu radiation source), the peak intensity derived from this crystal is the highest. That is, other crystal phases may be included in part.

[0038] <Compound 2 of the present invention>

[0039] Hereinafter, a compound of another example of the embodiment of the present invention (referred to as "Compound 2 of the present invention") will be described in detail.

[0040] Compound 2 of the present invention is a compound represented by the compositional formula Zr 2.00-b M b S Y P Z O 12.00+δ (where 0 ≤ b < 2.00, 0.30 ≤ Y ≤ 1.00, Z > 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition).

[0041] In the compositional formula of Compound 2 of the present invention, when b = 0, it becomes Zr 2.00 S Y P Z O 12.00+δ (where 0.30 ≤ Y ≤ 1.00, Z > 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition). On the other hand, when 0 < b < 2.00, it becomes a compound in which a part of the Zr sites is replaced by M.

[0042] In the composition formula of the present compound 2, M is preferably one or a combination of two or more selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, and Mo.

[0043] Zr 2.00 S Y P Z O 12.00+δ The compound in which a part of the Zr site in (wherein 0.30≤Y≤1.00, Z>2.00) is substituted with these elements M shows a negative thermal expansion coefficient similarly to the compound in which the Zr site contains only Zr, and can achieve high insulation resistance.

[0044] In the composition formula of the present compound 2, "b" representing the amount (atomic ratio) of the M element is preferably greater than 0 and less than 2.00, more preferably greater than 0 or less than 1.50, still more preferably greater than 0 or less than 1.00, and still more preferably greater than 0 or less than 0.80.

[0045] In the composition formula of the present compound 2, "Y" representing the amount (atomic ratio) of S (sulfur) is preferably 0.30 or more and 1.00 or less, more preferably 0.30 or more or 0.80 or less, and even more preferably 0.30 or more or 0.50 or less.

[0046] Furthermore, "Z" indicating the amount (atomic ratio) of P (phosphorus) needs to be greater than 2.00. On the other hand, it is preferably 3.50 or less, more preferably 3.00 or less, and even more preferably 2.80 or less.

[0047] In addition, "δ" in the composition formula of the present compound 2 is a value specified in a manner to satisfy the charge neutrality condition, and is usually -2.50 to 1.00. Sometimes, it is particularly -2.00 or more or 0.50 or less, more particularly -1.50 or more or 0.00 or less, more particularly -1.50 or more or -0.50 or less, and even more particularly more than -1.33 or less than -0.80. It should be noted that the "charge neutrality condition" may not be completely neutral, and oxygen deficiency and oxygen excess compositions within the range allowed as a compound are allowed.

[0048] The amount of each element except oxygen, that is, the amount of Zr, M, S and P can be measured by dissolving the total amount and using ICP-OES. In addition, strict measurement of the amount of oxygen is difficult, so it is set to use a composition ratio estimated to be electrically neutral by the chemical ratio of the elements except oxygen.

[0049] Examples of the crystal phase present in compound 2 include α-Zr2SP2O 12Phase (ICDD card number: 04-017-0937 or / and ICDD card number: 00-038-0489), preferably, the crystal is the main phase, that is, in the X-ray diffraction pattern obtained by analyzing compound 2 by X-ray diffraction method (XRD, Cu ray source), the peak intensity derived from the crystal is the highest. That is, other crystalline phases may also be included in a part.

[0050] <Surface treatment>

[0051] The present compounds 1 and 2 may both be surface-treated compounds.

[0052] Both of the present compounds 1 and 2 are surface-treated with a predetermined surface treatment compound, thereby improving insulation properties and chemical resistance, and contributing to improving wettability to resin.

[0053] As the surface treatment compound, in addition to silane coupling agents, aluminate coupling agents, titanate coupling agents, zirconium coupling agents, etc., organic compounds such as organic carboxylic acids and organic amines, and inorganic compounds such as silicon dioxide, aluminum oxide, zinc oxide, and titanium oxide can be used.

[0054] In particular, the use of a silane coupling agent as a surface treatment compound shows a remarkable effect of improving the insulation of the components constituting the compound of the present invention, preventing the elution of the components, and improving the wettability when mixed with a resin.

[0055] As for the above-mentioned silane coupling agent as a surface treatment agent, various silane coupling agents such as epoxy, amino, vinyl, methacrylic, acrylic, mercapto, and alkyl can be used. Specific examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 8-glycidoxyoctyltrimethoxysilane, 8-glycidoxyoctylmethyldimethoxysilane, 8-glycidoxyoctylmethyldiethoxysilane, 3-aminopropyltrimethoxysilane, vinyltrimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-Hexyl)ethyl triethoxysilane, p-phenylene trimethoxysilane, 3-methacryloxypropyl methyl trimethoxysilane, 3-acryloxypropyl trimethoxysilane, 3-ureidopropyl triethoxysilane, 3-mercaptopropyl trimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanate propyl triethoxysilane, methyl trimethoxysilane, dimethyl dimethoxysilane, methyl triethoxysilane, dimethyl diethoxysilane, phenyl triethoxysilane, n-propyl trimethoxysilane, n-propyl triethoxysilane, hexyl trimethoxysilane, hexyl triethoxysilane, octyl triethoxysilane, decyl trimethoxysilane, etc. These silane coupling agents may be used alone or in combination of two or more.

[0056] Examples of the carboxylic acids used as surface treatment agents include caproic acid (hexanoic acid), caprylic acid (octanoic acid), capric acid (decanoic acid), lauric acid (dodecanoic acid), myristic acid (tetradecanoic acid), palmitic acid (hexadecanoic acid), stearic acid (octadecanoic acid), oleic acid, linoleic acid, and linolenic acid.

[0057] The amines used as the surface treatment agent include aliphatic amines, etc. In particular, aliphatic amines having 6 to 18 carbon atoms, particularly 10 to 18 carbon atoms, can be preferably used. Specifically, hexylamine, octylamine, decylamine, laurylamine, oleylamine, stearylamine, etc. can be mentioned.

[0058] <d50>

[0059] The volume median diameter (D50) of Compounds 1 and 2 measured by laser diffraction scattering particle size distribution method is preferably 0.05 μm to 100 μm when the cumulative volume is 50% by volume.

[0060] If the D50 of Compounds 1 and 2 is 0.05 μm or more, for example, the dispersibility in a substrate such as resin becomes good, so it is preferred. If it is 100 μm or less, the smoothness of the molded body becomes good, so it is preferred.

[0061] From the above viewpoints, the D50 of Compounds 1 and 2 is more preferably 0.1 μm or more, further preferably 0.5 μm or more, and still further preferably 1 μm or more. On the other hand, it is more preferably 50 μm or less, further preferably 40 μm or less, and still further preferably 30 μm or less.

[0062] <BET specific surface area>

[0063] The BET specific surface area of Compounds 1 and 2 is preferably 1 m 2 / g to 50 m 2 / g.

[0064] If the BET specific surface area of Compounds 1 and 2 is 1 m 2 / g or more, for example, the smoothness of the molded body becomes good, so it is preferred. If it is 50 m 2 / g or less, for example, the dispersibility in a substrate such as resin becomes good, so it is preferred.

[0065] From the above viewpoints, the BET specific surface area of Compounds 1 and 2 is more preferably 2 m 2 / g or more, further preferably 5 m 2 / g or more, still further preferably 10 m 2 / g or more, and even still further preferably 15 m 2 / g or more. On the other hand, it is more preferably 45 m 2 / g or less.

[0066] <Volume resistivity>

[0067] Compounds 1 and 2 can set the volume resistivity to 2000 Ω·cm or more.

[0068] In the case of applications requiring insulation, a higher volume resistivity is preferred.

[0069] From such a viewpoint, the volume resistivity of the present compounds 1 and 2 is more preferably 10,000 Ω·cm or more, more preferably 100,000 Ω·cm or more, and even more preferably 1,000,000 Ω·cm or more.

[0070] <Negative thermal expansion coefficient>

[0071] The present compounds 1 and 2 show negative thermal expansion coefficients, for example, in a temperature range of 30°C to 100°C, a temperature range of 30°C to 200°C, a temperature range of 30°C to 300°C, and the like.

[0072] Among them, the present compound 1 shows a significantly excellent negative thermal expansion coefficient in the temperature range of 30°C to 100°C. Specifically, when heated from 30°C to 100°C, the volume at 100°C can shrink by 0.15% to 2.0% relative to the volume at 30°C. It is more preferably 0.15% to 1.0%, more preferably 0.15% to 0.70%, and even more preferably 0.15% to 0.45%.

[0073] In addition, the lower limit of each of the above ranges is 0.15%, but the lower limit is preferably 0.20%, and more preferably 0.25%.

[0074] On the other hand, the present compound 2 shows a significantly excellent negative thermal expansion coefficient particularly in the temperature range of 30°C to 200°C and the temperature range of 30°C to 300°C.

[0075] Specifically, when heated from 30°C to 200°C, the volume at 200°C may shrink by 1.0% to 3.0% relative to the volume at 30°C. More preferably, the volume may shrink by 1.0% to 2.0%, more preferably by 1.1% to 2.0%, and even more preferably by 1.1% to 1.5%. It should be noted that the lower limit of each range is 1.0%, but the lower limit is preferably 1.05%, and more preferably 1.1%.

[0076] Furthermore, when heated from 30°C to 300°C, the volume at 300°C may shrink by 1.0% to 3.0% relative to the volume at 30°C, more preferably by 1.0% to 2.0%, still more preferably by 1.1% to 2.0%, and still more preferably by 1.1% to 1.5%.

[0077] In addition, the lower limit of each of the above ranges is 1.0%, but the lower limit is preferably 1.05%, and more preferably 1.1%.

[0078] <Manufacturing method>

[0079] Next, the production method of the present compounds 1 and 2 will be described. However, the production method of the present compounds 1 and 2 is not limited to the production method described below.

[0080] As an example of a method for producing the present compounds 1 and 2, there can be cited a method for producing a compound, which is characterized in that a mixture containing at least a Zr raw material, a phosphorus raw material, sulfuric acid, water and a raw material of M of the above composition formula as required (referred to as "M raw material") is hydrothermally treated to obtain a hydrothermally treated mixture, the hydrothermally treated mixture is solid-liquid separated and washed to obtain a washed mixture, the washed mixture is dried to obtain a dried mixture, and the dried mixture is calcined at a temperature of 300 to 1000°C.

[0081] Hereinafter, the manufacturing method will be described sequentially.

[0082] As the Zr raw material, for example, zirconium oxychloride and its hydrate, zirconium chloride and its hydrate, zirconium oxyacetate and its hydrate, zirconium acetate and its hydrate, zirconium sulfate and its hydrate, zirconium oxynitrate and its hydrate, zirconium nitrate and its hydrate, zirconium carbonate and its hydrate, ammonium zirconium carbonate and its hydrate, sodium zirconium carbonate and its hydrate, potassium zirconium carbonate and its hydrate, etc. can be used. However, it is not limited to the above.

[0083] As the phosphorus raw material, phosphoric acid (H3PO4), diammonium hydrogen phosphate ((NH4)2HPO4), diammonium phosphate (NH4H2PO4), ammonium phosphate (NH4(PO4)3), pyrophosphoric acid, and polyphosphoric acid can be used. However, they are not limited to the above.

[0084] Examples of the M raw material include compounds containing the element M, such as sulfates and solutions thereof, chloride salts and solutions thereof, nitrates, acetates, oxides, polyacids and salts thereof of the element M. For example, when M is Ti, examples include titanium (IV) sulfate solution (Ti(SO4)2) and titanium (IV) chloride solution (TiCl4); when M is Ce, examples include cerium sulfate (Ce(SO4)2) and cerium chloride (CeCl3); when M is Sn, examples include stannous chloride, tin chloride, tin sulfate, and tin oxide (SnO2); when M is Mn, examples include manganese dioxide (MnO2); when M is W, examples include tungsten trioxide (WO3) and ammonium paratungstate ((NH4) 10 (H2W 12 O 42 )), when M is Mo, examples thereof include molybdenum trioxide (MoO3), hexaammonium heptamolybdate ((NH4)6Mo7O 24 ), diammonium molybdate ((NH4)2MoO4). However, it is not limited to the above. It should be noted that the above compounds are described as anhydrous, but also include hydrates.

[0085] If necessary, as a S (sulfur) raw material, for example, ammonium sulfate, sulfur powder, etc. may be blended.

[0086] The Zr raw material, phosphoric acid, the M raw material as required, sulfuric acid, and water are mixed and stirred, and the obtained aqueous solution (mixture) is subjected to a hydrothermal treatment to obtain a mixture after the hydrothermal treatment.

[0087] At this time, regarding the phosphorus raw material (P raw material) and the Zr raw material, the P / Zr molar ratio may be set to be the same as that of the target compound, or the phosphorus raw material may be increased.

[0088] As a method for the hydrothermal treatment, for example, the aqueous solution (mixture) is placed in a sealable container, heated to 100 to 230° C., and allowed to stand under pressure for 3 hours to 3 days for the hydrothermal treatment.

[0089] Next, the mixture after the hydrothermal treatment is subjected to solid-liquid separation and washing to obtain a washed mixture. That is, after the solid-liquid separation, washing is performed by further adding water for solid-liquid separation or washing with water. At this time, it is preferred to wash repeatedly as needed.

[0090] This washing can wash away the excess S component.

[0091] Next, the washed mixture is dried to obtain a dried mixture.

[0092] In this case, for example, the washed mixture may be dried by heating it so that its product temperature becomes 60 to 150° C. The drying method may be appropriately adopted.

[0093] Furthermore, it was confirmed that, for example, when a box-type dryer such as ETTAS constant temperature dryer manufactured by AS ONE is used, the set temperature of the drying device is substantially the same as the product temperature.

[0094] Next, the dried mixture is calcined to produce the present compound.

[0095] At this time, the dried mixture can be calcined in the following manner: the product temperature is maintained at 300-1000°C, particularly at 400°C or above or 1000°C or below, particularly at 400°C or above or 800°C or below, for 1-24 hours.

[0096] Furthermore, it was confirmed that, for example, when a box-type electric furnace such as the KBF1150°C series electric furnace manufactured by KOYO THERMOS SYSTEMS is used, the set temperature of the sintering device, that is, the temperature inside the furnace, is substantially the same as the product temperature.

[0097] Furthermore, when performing a surface treatment, the surface treatment may be performed after crushing or pulverizing as necessary after the above-mentioned calcination.

[0098] The surface treatment may be performed using the above-mentioned surface treatment compound.

[0099] As for the specific method of the surface treatment, the present compounds 1 and 2 may be mixed with the surface treatment compound in a dry manner or in a wet manner.

[0100] Wet mixing can be carried out using water, a mixed solvent obtained by mixing water and a water-soluble organic solvent within a range of solubility in water, an organic solvent, or the like.

[0101] However, the production method of the present compounds 1 and 2 is not limited to the above-mentioned production method.

[0102] <Purpose>

[0103] The present compounds 1 and 2 can form a composite material with controlled thermal expansion coefficient by mixing a negative thermal expansion material with a material having a positive thermal expansion coefficient (positive thermal expansion material), in other words, by dispersing the negative thermal expansion material in the positive thermal expansion material.

[0104] Examples of the positive thermal expansion material include resin materials, metal materials, and ceramic materials.

[0105] <Description of statement>

[0106] In the present specification, when expressed as "α to β" (α and β are arbitrary numbers), unless otherwise specified, it includes the meaning of "greater than α and less than β", and also includes the meaning of "preferably greater than α" or "preferably less than β".

[0107] Furthermore, when expressed as “α or more” (α is an arbitrary number) or “β or less” (β is an arbitrary number), it also includes the meaning of “preferably greater than α” or “preferably less than β”.

[0108] Example

[0109] The present invention is further described by the following examples. However, the following examples are not intended to limit the present invention in any way.

[0110] <Example 1>

[0111] ZrCl2O·8H2O and phosphoric acid (H3PO4) were dissolved in distilled water to a concentration of 0.8 mol / L and then mixed. Next, 20 ml of each of these aqueous solutions was mixed with 6 ml of 98% H2SO4 and stirred for 90 minutes using a stirrer.

[0112] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0113] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer set at an atmosphere temperature of 110°C.

[0114] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0115] <Example 2>

[0116] ZrCl2O·8H2O and phosphoric acid (H3PO4) were dissolved in distilled water to 0.8 mol / L respectively and then mixed. Next, 20 ml of each of these aqueous solutions was mixed with 4.5 ml of 98% H2SO4 and stirred for 90 minutes using a stirrer.

[0117] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0118] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0119] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0120] <Reference Example 1>

[0121] ZrCl2O·8H2O and NH4H2PO4 were dissolved in distilled water to a concentration of 0.8 mol / L, respectively. Then, 20 ml of each of these aqueous solutions was mixed with 6 ml of 98% H2SO4, and stirred for 90 minutes using a stirrer.

[0122] After that, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), and placed in a pressure-resistant stainless steel outer cylinder. Then, the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and this state was maintained at 180° C. for 2 days for hydrothermal treatment.

[0123] After the hydrothermal treatment, a white precipitate was generated in the Teflon (registered trademark) container taken out. The solution containing the precipitate was poured into an evaporating dish and heated on a heater at about 100°C to evaporate the excess water. The evaporating dish was further dried in an electric furnace at 300°C for 12 hours. After that, the sample dried at 300°C (product temperature) was further calcined in an electric furnace at 500°C (product temperature) for 4 hours to obtain a compound (sample).

[0124] <Reference Example 2>

[0125] A compound (sample) was obtained in the same manner as in Reference Example 1 except that the calcination temperature was set to 700° C. (sample temperature).

[0126] <Example 3>

[0127] 20 ml of an aqueous solution of ZrCl2O·8H2O prepared at 0.8 mol / L was mixed with 20 ml of an aqueous solution of ammonium dihydrogen phosphate (NH4H2PO4) prepared at 1.1 mol / L. Then, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0128] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0129] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0130] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0131] <Example 4>

[0132] 20 ml of an aqueous solution of ZrCl2O·8H2O prepared at 0.8 mol / L was mixed with 20 ml of an aqueous solution of ammonium dihydrogen phosphate (NH4H2PO4) prepared at 0.9 mol / L. Then, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0133] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0134] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0135] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0136] <Example 5>

[0137] To 5 g of the compound (sample) obtained by the same steps as in Example 1, 0.21 g of 3-isocyanatepropyltriethoxysilane as a silane coupling agent was added as a surface treatment compound, mixed for 2 minutes using a mixer (Force Mill FM-1 manufactured by OSAKA CHEMICAL), and then heat treated at 140° C. for 1 hour to obtain the compound (sample).

[0138] <Example 6>

[0139] To 5 g of the compound (sample) obtained by the same procedure as in Example 3, 0.20 g of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent was added as a surface treatment compound, mixed with a mixer for 2 minutes, and then heat treated at 140° C. for 1 hour to obtain a compound (sample).

[0140] <Example 7>

[0141] To 5 g of the compound (sample) obtained by the same procedure as in Example 3, 0.19 g of hexyltrimethoxysilane as a silane coupling agent was added as a surface treatment compound, mixed for 2 minutes using a mixer 4, and then heat treated at 140°C for 1 hour to obtain a compound (sample).

[0142] <Example 8>

[0143] 1.28 g of 30% titanium sulfate solution was added to 20 ml of an aqueous solution prepared with ZrCl2O·8H2O at 0.72 mol / L and mixed. 20 ml of an aqueous solution prepared with ammonium dihydrogen phosphate (NH4H2PO4) at 0.9 mol / L was mixed therein. Then, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0144] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0145] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0146] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0147] <Example 9>

[0148] 2.56 g of 30% titanium sulfate solution was added to 20 ml of an aqueous solution prepared with ZrCl2O·8H2O at 0.64 mol / L and mixed. 20 ml of an aqueous solution prepared with ammonium dihydrogen phosphate (NH4H2PO4) at 0.9 mol / L was mixed therein. Next, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0149] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0150] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0151] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0152] <Example 10>

[0153] 0.61 g of CeCl3·7H2O was added to 20 ml of an aqueous solution prepared with ZrCl2O·8H2O at 0.72 mol / L and mixed. 20 ml of an aqueous solution prepared with ammonium dihydrogen phosphate (NH4H2PO4) at 0.9 mol / L was added thereto. Next, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0154] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0155] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0156] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0157] <Example 11>

[0158] 1.22 g of CeCl3·7H2O was added to 20 ml of an aqueous solution prepared with ZrCl2O·8H2O at 0.64 mol / L and mixed. 20 ml of an aqueous solution prepared with ammonium dihydrogen phosphate (NH4H2PO4) at 0.9 mol / L was mixed therein. Next, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0159] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0160] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0161] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0162] <Example 12>

[0163] 1.57 g of ammonium paratungstate pentahydrate was added to 20 ml of an aqueous solution prepared with ammonium dihydrogen phosphate (NH4H2PO4) at 0.9 mol / L, and the mixture was added to 20 ml of an aqueous solution prepared with ZrCl2O·8H2O at 0.72 mol / L and mixed. Next, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0164] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0165] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at an atmosphere of 110°C.

[0166] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0167] <Example 13>

[0168] 0.90 g of hexaammonium heptamolybdate tetrahydrate was added to 20 ml of an aqueous solution prepared with ammonium dihydrogen phosphate (NH4H2PO4) at 0.9 mol / L, and the mixture was added to 20 ml of an aqueous solution prepared with ZrCl2O·8H2O at 0.72 mol / L and mixed. Subsequently, 6 ml of 98% H2SO4 was mixed into the aqueous solution and stirred for 90 minutes using a stirrer.

[0169] Next, the stirred aqueous solution (mixture) was injected into a sealed container made of Teflon (registered trademark), placed in a pressure-resistant stainless steel outer cylinder, and then the container placed in the outer cylinder was placed in a hot air circulation oven for heating, and the state was maintained at 130° C. for 12 hours for hydrothermal treatment.

[0170] After the hydrothermal treatment, solid-liquid separation was performed, the supernatant was removed, and water was added to repeat the solid-liquid separation and washing, and then poured into an evaporating dish, and the solid content was heated and dried in a hot air dryer at 110°C.

[0171] The dried powder was placed in an electric furnace and calcined so as to be maintained at 500° C. (sample temperature) for 4 hours to obtain a compound (sample).

[0172] (Composition Analysis)

[0173] The composition (atomic ratio) of the prepared compound (sample) was analyzed using ICP-OES (Inductivity Coupled Plasma Optical Emission Spectrometry).

[0174] =ICP-OES=

[0175] ICP-OES device used: 700 series, ICP-OES (Agilent Technologies, Inc.)

[0176] (D50)

[0177] The prepared compound (sample) was placed in pure water and irradiated with ultrasound (40 W, 3 minutes) to disperse it, and then the volume cumulative particle size D50 when the cumulative volume was 50% by volume was measured using a particle size distribution measuring device ("Microtrac (trade name) MT-3300EXII (model)" manufactured by Microtrac BEL Co., Ltd.) using a laser diffraction scattering particle size distribution measuring method.

[0178] (BET specific surface area)

[0179] The BET specific surface area (SSA (BET)) of the prepared compound (sample) was measured using a specific surface area measuring device (Macsorb (HM model-1201) manufactured by MOUNTECH Co., Ltd.) in accordance with "6.2 Flow method (3.5) One-point method" of JIS R1626:1996 (Measurement method of specific surface area of ​​fine ceramic powder by gas adsorption BET method). At this time, a mixed gas of helium as a carrier gas and nitrogen as an adsorbate gas was used. In addition, the degassing conditions were set to 300°C × 10 minutes.

[0180] (Volume resistivity)

[0181] The prepared compound (sample) was compressed at a pressure of 63 MPa using a powder resistance measurement system MCP-PD51 manufactured by Mitsubishi Chemical Analytech, and the volume resistivity was measured by a four-terminal method. For samples exceeding the upper limit of the measurement of the device, pellets compressed at a pressure of 63 MPa were prepared separately and measured using a high resistance meter Hiresta UX / MCP-HT800 manufactured by Mitsubishi Chemical Analytech.

[0182] (Thermal expansion coefficient)

[0183] The expansion rate of the lattice volume of the prepared compound (sample) was measured by the following method.

[0184] The multi-purpose sample high temperature device unit was installed on the powder X-ray diffractometer described below, and the X-ray diffraction pattern was measured at 30° C. and 100° C. The measurement was started after the target temperature was reached and the sample was left to stand for 10 minutes.

[0185] The crystal structure was refined using the obtained X-ray diffraction pattern and analysis software (PDXL2), and the lattice constant at each temperature was calculated. The lattice volume was calculated from the lattice constant.

[0186] The table shows the lattice volume expansion coefficient from 30 to 100°C, that is, the ratio of the change in the lattice volume at 100°C (called "100°C volume") is calculated based on the lattice volume at 30°C (called "30°C volume"), that is, ((30°C volume - 100°C volume) / 30°C volume) × 100 as the volume expansion coefficient (%).

[0187] Similarly, the lattice volume expansion coefficient at 30 to 200° C. and the lattice volume expansion coefficient at 30 to 300° C. were calculated and shown in the table.

[0188] [High temperature XRD]

[0189] ·Using device: Ultima IV (Rigaku Co., Ltd.)

[0190] Atmosphere: Air

[0191] Tube current / tube voltage: 40kV / 40mA

[0192] Target: Cu

[0193] Stepping amplitude: 0.02°

[0194] ·Measurement range (scanning speed): 10~80°(4° / min)

[0195] ·Measurement temperature: 30℃, 100℃, 200℃, 300℃

[0196] [Table 1]

[0197]

[0198] [Table 2]

[0199]

[0200] From the above-mentioned embodiments and the test results conducted so far by the inventors of the present invention, it can be seen that: 2.00-b M b S Y P Z O 12.00+δ (wherein, M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, and Mo; 0 ≤ b < 2.00, 0 < Y < 0.30, Z ≥ 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition) the present compound 1, and the composition formula Zr 2.00-b M b S Y P Z O 12.00+δ (wherein, M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, and Mo; 0 ≤ b < 2.00, 0.30 ≤ Y ≤ 1.00, Z > 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition) the present compound 2 both exhibit a negative thermal expansion rate and have excellent insulation resistance.

[0201] It was confirmed that in the diffraction patterns obtained by X-ray diffraction of the compounds obtained in Examples 1, 2, and 5 above, there was an α-Zr2SP2O 12 phase (ICDD card number: 00-038-0489) as the main phase.

[0202] It was confirmed that in the diffraction patterns obtained by X-ray diffraction of the compounds obtained in Examples 3, 4, 6-13 and the reference example above, there was an α-Zr2SP2O 12 phase (ICDD card number: 04-017-0937) as the main phase.

[0203] Regarding the negative thermal expansion rate, it was found that both the present compounds 1 and 2 exhibit a negative thermal expansion rate in the temperature ranges of 30 to 100 °C, 30 to 200 °C, and 30 to 300 °C.

[0204] In particular, it was found that the present compound 1 exhibits a significantly excellent negative thermal expansion rate in the temperature range from room temperature (30 °C) to 100 °C.

[0205] For example, Examples 1, 2, 5, and 9 compared with Reference Examples 1 and 2 are characterized by having a smaller amount of S (Y) and a larger amount of P. It was confirmed that Examples 1, 2, 5, and 9 exhibit a more excellent negative thermal expansion rate in the temperature range of 30 °C to 100 °C. It is speculated that this is because: when the atomic ratio of S (Y) is less than 0.30 and the atomic ratio of P (Z) is 2.00 or more, the structure of the compound is stable, and a significantly excellent negative thermal expansion rate is exhibited in the temperature range from room temperature (30 °C) to 100 °C.

[0206] On the other hand, it is known that this Compound 2 exhibits significantly excellent negative thermal expansion rates in the temperature range from room temperature (30 °C) to 200 °C and in the temperature range from room temperature (30 °C) to 300 °C.

[0207] For example, compared with Reference Examples 1 and 2, Examples 3, 4, 6 - 8, 10 - 13 have a smaller amount of S (Y) and a larger amount of P. On the other hand, compared with Examples 1 and 2, they are characterized by a larger amount of S (Y) and a larger amount of P. Moreover, it was confirmed that these Examples 3, 4, 6 - 8, 10 - 13 exhibit more excellent negative thermal expansion rates in the temperature range from 30 °C to 200 °C and in the temperature range from 30 °C to 300 °C. It is speculated that this is because, when the atomic ratio of S (Y) is 0.30 - 1.00 and the atomic ratio of P (Z) is greater than 2.00, significantly excellent negative thermal expansion rates are exhibited in the temperature range from room temperature to 200 °C and in the temperature range from room temperature to 300 °C.

[0208] In addition, regarding the compounds represented by the compositional formula: Zr 2.00 S Y P Z O 12.00+δ (where 0 < Y < 0.30, Z ≥ 2.00) and Zr 2.00 S Y P Z O 12.00+δ (where 0.30 ≤ Y ≤ 1.00, Z > 2.00), from the knowledge disclosed in the above Patent Document 2 (WO2019 / 167924A1) and the like, it can be speculated that compounds obtained by substituting a part of the Zr sites with elements such as Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, Mo also exhibit negative thermal expansion rates in the same manner as the above compounds and can achieve high insulation resistance.

Claims

1. A compound represented by the compositional formula Zr 2.00-b M b S Y P Z O 12.00+δ wherein M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, and Mo; 0 ≤ b < 2.00, 0 < Y < 0.30, Z ≥ 2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition.

2. A compound having a composition formula of Zr 2.00-b M b S Y P Z O 12.00+δ Represents, wherein M is at least one selected from Ti, Ce, Sn, Mn, Hf, Ir, Pb, Pd, Cr, W, and Mo, 0≤b<2.00, 0.30≤Y≤1.00, Z>2.00, and δ is a value determined in a manner that satisfies the charge neutrality condition.

3. The compound according to claim 1, characterized in that It shows a negative thermal expansion rate.

4. The compound according to claim 2, characterized in that It exhibits a negative thermal expansion rate.

5. The compound according to claim 1 or claim 3, characterized in that When heated from 30°C to 100°C, the volume at 100°C shrinks by 0.15% to 2.0% relative to the volume at 30°C.

6. The compound according to claim 2 or claim 4, characterized in that When heated from 30°C to 200°C, the volume at 200°C shrinks by 1.0% to 3.0% relative to the volume at 30°C.

7. The compound according to any one of claims 1 to 4, characterized in that When heated from 30°C to 300°C, the volume at 300°C shrinks by 1.0% to 3.0% relative to the volume at 30°C. 8 . The compound according to claim 1 , which has a volume resistivity of 2000 Ω·cm or more. 9 . The compound according to claim 1 , wherein the cumulative volume particle diameter D50 when the cumulative volume is 50% by volume as measured by laser diffraction scattering particle size distribution measurement is 0.05 μm to 100 μm.

10. The compound according to any one of claims 1 to 4, which has a BET specific surface area of ​​1 m 2 / g~50m 2 / g. 11 . The compound according to claim 1 , which is surface-treated with a surface-treating compound.

12. The compound according to claim 11, wherein The surface treatment compound is a silane coupling agent. 13 . A composite material, which is obtained by mixing the compound according to claim 1 with a positive thermal expansion material or / and dispersing the compound in the positive thermal expansion material.

14. A method for producing a compound, characterized in that: This is a method for producing the compound according to any one of claims 1 to 10, wherein a mixture containing at least a Zr raw material, a phosphorus raw material, sulfuric acid, water and a raw material of the composition formula M as required is subjected to hydrothermal treatment to obtain a hydrothermally treated mixture, the hydrothermally treated mixture is subjected to solid-liquid separation and washing to obtain a washed mixture, the washed mixture is dried to obtain a dried mixture, and the dried mixture is calcined at a temperature of 300 to 1000°C.

15. A method for producing a compound, characterized in that: This is a method for producing the compound according to claim 11 or 12, wherein a mixture containing at least a Zr raw material, a phosphorus raw material, sulfuric acid, water and a raw material of the composition formula M as required is subjected to hydrothermal treatment to obtain a hydrothermally treated mixture, the hydrothermally treated mixture is subjected to solid-liquid separation and washing to obtain a washed mixture, the washed mixture is dried to obtain a dried mixture, the dried mixture is calcined at a temperature of 300 to 1000°C, and then surface treated using a surface treatment compound.

Citation Information

Patent Citations

  • Negative thermal expandable material, and complex

    JP2017048071A

  • Negative thermal expansion materials

    US5514360A

  • Negative thermal expansion material, composite material, and method for producing negative thermal expansion material

    WO2019167924A1